Phenotypic characterization of temperature-sensitive mutants of vaccinia virus with mutations in a 135,000-Mr subunit of the virion-associated DNA-dependent RNA polymerase. - Ensinger, M J (1987)
The phenotypic defects of three temperature-sensitive (ts) mutants of vaccinia virus, the ts mutations of which were mapped to the gene for one of the high-molecular-weight subunits of the virion-associated DNA-dependent RNA polymerase, were characterized. Because the virion RNA polymerase is required for the initiation of the viral replication cycle, it has been predicted that this type of mutant is defective in viral DNA replication and the synthesis of early viral proteins at the nonpermissive temperature. However, all three mutants synthesized both DNA and early proteins, and two of the three synthesized late proteins as well. RNA synthesis in vitro by permeabilized mutant virions was not more ts than that by the wild type. Furthermore, only one of three RNA polymerase activities that was partially purified from virions assembled at the permissive temperature displayed altered biochemical properties in vitro that could be correlated with its ts mutation: the ts13 activity had reduced specific activity, increased temperature sensitivity, and increased thermolability under a variety of preincubation conditions. Although the partially purified polymerase activity of a second mutant, ts72, was also more thermolabile than the wild-type activity, the thermolability was shown to be the result of a second mutation within the RNA polymerase gene. These results suggest that the defects in these mutants affect the assembly of newly synthesized polymerase subunits into active enzyme or the incorporation of RNA polymerase into maturing virions; once synthesized at the permissive temperature, the mutant polymerases are able to function in the initiation of subsequent rounds of infection at the nonpermissive temperature.